2022
DOI: 10.3390/life12101564
|View full text |Cite
|
Sign up to set email alerts
|

Blue-LED-Light Photobiomodulation of Inflammatory Responses and New Tissue Formation in Mouse-Skin Wounds

Abstract: Background: Recent studies evidence that blue-LED-light irradiation can modulate cell responses in the wound healing process within 24 hours from treatment. This study aims to investigate blue-light (410–430 nm) photobiomodulation used in a murine wound model within six days post-treatment. Methods: A superficial wound was made in 30 CD1 male mice. The injuries were treated with a blue LED light (20.6 J/cm2), and biopsies were collected at 24, 72, and 144 hours. Histology, fluorescence analysis, and advanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Blue light PBM has been shown to modulate the oxidative state of Cytochrome C and thus in uence the process of cellular respiration, which is more essential than ever in cells involved in tissue repair 9,10 . Furthermore, Blue Light acts on in ammation by stimulating a more rapid transition; this e ect has been demonstrated in preclinical studies where early arrival of in ammatory in ltrate cells in the wound bed and an acceleration of the phenotypic switch of macrophages (M1 to M2), marking the transition to the proliferative phase, has been recorded in treated wounds 11,12 . These e ects of Blue Light PBM are considered to be primally responsible for wound healing.…”
Section: Resultsmentioning
confidence: 92%
“…Blue light PBM has been shown to modulate the oxidative state of Cytochrome C and thus in uence the process of cellular respiration, which is more essential than ever in cells involved in tissue repair 9,10 . Furthermore, Blue Light acts on in ammation by stimulating a more rapid transition; this e ect has been demonstrated in preclinical studies where early arrival of in ammatory in ltrate cells in the wound bed and an acceleration of the phenotypic switch of macrophages (M1 to M2), marking the transition to the proliferative phase, has been recorded in treated wounds 11,12 . These e ects of Blue Light PBM are considered to be primally responsible for wound healing.…”
Section: Resultsmentioning
confidence: 92%
“…For example, in a recent study, Magni et al could show that blue light (410–420 nm; 20.6 J/cm 2 , 0.69 W/cm 2 ) induces a quicker healing process in a mouse model. The authors suggested that the photobiomodulation of the wounds with blue light evokes a mast cell response, which, in turn, stimulates an early inflammatory response, angiogenesis, and myofibroblast differentiation [ 59 ]. In patients ( n = 12) with systemic sclerosis skin ulcers, the weekly treatment of the ulcers with blue light (400–430 nm, 120 mW/cm 2 , 7.2 J/cm 2 ), in addition to the standard therapy, showed significant improvements after 8 weeks [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, LED light is noncoherent, so for LLLT so it is not as selective in delivering high energy to the target tissue. Thirdly, the light is non-collimated, and this makes it very difficult to focus it into a fiber optic cable for endoscopic and internal applications (For more details see: [64][65][66]). On the other hand, LEDs have many advantages, apart from the cost, are easy used, induce less damage, could be portable and used at home, are painless and can work in different wavelengths at the same time [64][65][66][67].…”
Section: Impairment Of Wound Healing and Recent Therapeutic Strategiesmentioning
confidence: 99%
“…Thirdly, the light is non-collimated, and this makes it very difficult to focus it into a fiber optic cable for endoscopic and internal applications (For more details see: [64][65][66]). On the other hand, LEDs have many advantages, apart from the cost, are easy used, induce less damage, could be portable and used at home, are painless and can work in different wavelengths at the same time [64][65][66][67]. Photobiomodulation have been used as complementary therapy of CW, mostly in the initial phases, in which other physical therapies are difficult to apply, decreasing the inflammatory stage and leading to a modulate proliferation and targeting the biofilm [62].…”
Section: Impairment Of Wound Healing and Recent Therapeutic Strategiesmentioning
confidence: 99%